Building Information Modelling (BIM) dalam Aspek Pengurusan Kewangan Projek Pembinaan - Shahrodin, Mohamad Firdaus; Ahmad Latiffi, Aryani (Research in Management of Technology and Business, 2021)
Financial management is a process that involves the planning and distribution of manpower, capital (cash), goods (assets), and services to meet the goals of an organization. Also, it is a process in which an organization needs to follow certain steps to obtain and subsequently distribute resources based on specific priorities. Building information modeling (BIM) has been identified as a mechanism that can assist the financial management system. The objectives of this study are to examine the importance of the use of BIM in improving the financial management aspects of construction projects and to identify measures to encourage the use of BIM among industry players to improve the financial aspects of construction projects. This study was conducted through a quantitative method by the survey through a questionnaire. The respondents involved in this study are quantity surveyors working in G7 grade construction companies in Johor Bahru, Johor. Questionnaires are distributed online using Google Forms. Data findings from the questionnaire were analyzed using the Software of Statistical Package for the Social Sciences (SPSS). The results show that the use of BIM can help in the financial management aspects of construction projects such as using BIM software can control the entire construction cost by providing the total cost of each construction phase. The study also shows that a framework of BIM implementation measures in financial management practices in Malaysia has been formed. The implementation of BIM in this aspect can be improved by CIDB needs to hold seminars or courses related to the use of BIM to the financial managers of each company to increase the level of knowledge using BIM software. In conclusion, this study can be used as a reference to the financial manager as well as other relevant parties to manage the finance of construction projects.